Role of nitric oxide in predicting radiotherapy-related side effects in patients with cervical cancer - Gul D.; Ozyurt H.; Gumustekin Bulbul O.; MAYADAĞLI A. (My University, 2025)
Objective: To assess whether serum nitric oxide (NO) levels can predict radiation-induced side effects in cervical cancer patients undergoing pelvic radiotherapy (RT). Patients and Methods: Twenty participants diagnosed with locally advanced-stage cervical cancer were included. Weekly blood samples were analyzed for NO levels. Genitourinary (GU), lower gastrointestinal (LGI), and upper gastrointestinal (UGI) toxicities were graded weekly. Two separate analyses were conducted based on initial NO levels either categorized as NO-low and NO-high or the mean NO ratios (NOR) recorded before and after RT. Lastly, the mean clinical symptoms (grade < 2 versus grade ≥ 2) at the end of RT were correlated with the mean NO values. Results: Serum NO levels increased significantly from baseline (p = 0.001). No significant differences in toxicity were found when comparing mean NOR values before and after RT. Symptomatic patients (grade ≥ 2) exhibited higher NO levels at week 5 for GU and LGI toxicities. Baseline NO levels did not consistently predict the severity of side effects. Conclusion: Serum NO levels increased significantly during RT. No definitive correlation with toxicity severity and NO levels were observed. Further studies require to clarify the potential of NO as a biomarker for predicting RT-induced side effects.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (Med); Klinik Tıp; Tıp Genel & Dahili; Clinical Medicine (Med); Clinical Medicine; Medicine General & Internal; Genel Tıp; General Medicine; Cervical cancer; Nitric oxide; Predictive; Radiotherapy; Side effects